Kebijakan Hukum Pidana Terhadap Tindak Pidana Kepemilikan Senjata Api Oleh Masyarakat Sipil - Termature, Marlen; Sopacua, Margie Gladis; Latumaerissa, Denny (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Possession and misuse of firearms by civilians is a very dangerous and potentially dangerous matter. How firearms can cause the death of a person or many people. Even though firearms are very important for national defense and security, firearms can usually cause very detrimental consequences for individuals and society if they are misused or used not in accordance with applicable regulations. Therefore, this paper aims to determine the legal policies implemented regarding the ownership of firearms by civilians. The research method used in this writing is Normative Juridical, the problem approach used is the statutory approach, case approach and conceptual approach, the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The procedure for collecting legal materials in this writing was carried out using the literature study method, the processing of legal materials in this writing was carried out by systematizing the legal materials by carrying out selection of legal materials and the analysis used in this writing used qualitative analysis methods. The result of the discussion of this writing is to explain one form of criminal law policy, namely Formulation Policy. Formulation Policy is a step taken by the state to formulate any actions that are considered disgraceful, then use criminal law as an effort to overcome actions that are considered disgraceful, so that people stay away from them or do not commit these actions. However, in reality, the current criminal law formulation policy, especially regarding the current Policy for Formulating the Crime of Illegal Firearms Possession, has a number of fundamental weaknesses, thus affecting the level of effectiveness in the implementation of eradicating the crime of Illegal Firearms Possession, due to weaknesses in the formulation stage (in abstracto) is a strategic weakness for the next stage, namely the application and execution stage (in concrete). Apart from that, there are many law enforcement efforts carried out related to criminal acts of possession of firearms by civil society, including: preventive efforts and repressive efforts. In efforts to enforce the law, the obstacles encountered are: internal obstacles and external obstacles.